Students’ Perception Towards The Use Of Zoom Meeting For Online Learning In Teaching English Speaking Skill In Times Of Covid-19 - Putri, Nanda Amalia; Suryaman, Maman (Jurnal Ilmiah Mandala Education (JIME), 2024)
This article examines students’ perception of using Zoom Meeting for online learning in teaching English speaking skill. Qualitative descriptive method was used to find out students’ perception related to the use of Zoom Meeting during learning speaking. The data collection used was collected by creating a questionnaire that consisted of 15 statements. The questionnaire was distributed via Google Form. The participants of this study were students of English Education Department from Singaperbangsa Karawang University which is selected randomly about 9 students from second semester students. The result showed that the use of Zoom Meeting for online learning in teaching English speaking skills give positive and negative impacts. Zoom Meeting applications make them understand some speaking class learning materials easily. However, in the other case, most of the students were bored with the implementation of online classes and lost of motivation to study during the COVID-19 pandemic.